Audit of the quality of medical care as a way to improve the efficiency of medical organizations - Svetlana A. Mukhortova; Tatiana V. Kulichenko; Leyla S. Namazova-Baranova; Svetlana G. Piskunova; Elena A. Besedina; Dmytrij V. Prometnoy (Union of pediatricians of Russia, 2017)
The article analyzes the possibilities of auditing the quality of medical care to improve the efficiency of medical organizations. The audit of the medical organization is a closed cycle to improve the quality of medical care, which should include assessing the actual assistance provided in relation to the approved high quality standards, developing a plan to bring the actual level of medical care into compliance with the declared standards, and improving this assistance to achieve the best health indicators. The review examines the different forms of clinical audit and the experience of their use in various countries of the world.